The evolution of presentational changes to Corporate social responsibility disclosures: An historic analysis of an electricity company - Ruane, Helen; Quinn, Martin (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2018)
While Corporate Social Responsibility (CSR) and associated reporting has been studied extensively, little research has been done from a longitudinal perspective. This paper explores the presentational changes in CSR disclosures in the annual reports of an electricity company over the period from 1986 to 2017 using themes and methods drawn from extant research. The analysis shows changes are in general reflective of external factors such as legislation, economic crises, CSR frameworks and the organisation’s competitive environment. A more stable level of CSR reporting is apparent since about 2010, and the levels are substantially higher in more recent years